2011
DOI: 10.1111/j.1525-142x.2011.00472.x
|View full text |Cite
|
Sign up to set email alerts
|

A hexamer origin of the echinoderms' five rays

Abstract: Of the major deuterostome groups, the echinoderms with their multiple forms and complex development are arguably the most mysterious. Although larval echinoderms are bilaterally symmetric, the adult body seems to abandon the larval body plan and to develop independently a new structure with different symmetries. The prevalent pentamer structure, the asymmetry of Lovén's rule and the variable location of the periproct and madrepore present enormous difficulties in homologizing structures across the major clades… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…In adult crinoids, the mouth and anus form in the central region of the hydrocoel ring (ring canal) and on the CD interray, respectively (de Lussanet ). Therefore, the anterior and posterior sides of the postlarva correspond to the sides of the A radius and CD interradius, respectively (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In adult crinoids, the mouth and anus form in the central region of the hydrocoel ring (ring canal) and on the CD interray, respectively (de Lussanet ). Therefore, the anterior and posterior sides of the postlarva correspond to the sides of the A radius and CD interradius, respectively (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In the feather star T. carinata , unlike M. rotundus , the opening of the crescent is at the left side (Mortensen, ). The juvenile mouth forms in the central region of the hydrocoel ring in echinoderms (de Lussanet, ; Lacalli, ) including the sea lily (Amemiya et al, ). At the cystidean stage in M. rotundus , the crescent‐shaped hydrocoel located in the oral‐top region had five radial lobes (A–E in Carpenter's system) (Carpenter, ) in its lumen (Amemiya et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous developmental studies have confirmed that developmental series can be useful for understanding the origins and identities of novel characters over a broad range of taxa (Marden & Kramer ; Dehal et al. ; Smith ; de Lussanet ; Heers & Dial ; Page ).…”
mentioning
confidence: 94%